Modulation of inspiratory drive to phrenic motoneurons by presynaptic adenosine A1 receptors - Dong, XW (J Neurosci, 1995)
The involvement and mechanisms of adenosine A1 receptors in regulating bulbospinal synaptic transmission of inspiratory drive to phrenic motoneurons were investigated. The adenosine analog N6- cyclopentyladenosine (CPA) induced a dose-dependent decrease of both inspiratory-modulated activity of C4 ventral roots and synaptic currents of phrenic motoneurons in an in vitro brainstem/spinal cord preparation from neonatal rats. No significant changes were observed in steady-state membrane current (during the expiratory phase). The depressant action of CPA on inspiratory drive was blocked by the selective A1 receptor antagonist 8-cyclopentyltheophylline (CPT). The adenosine receptor antagonist 3-isobutyl-1-methylxanthine (IBMX) induced varying degrees of enhancement of inspiratory-modulated synaptic current, as did CPT. This suggests a role of endogenous adenosine in synaptic transmission of respiratory drive to phrenic motoneurons. The relative contribution of pre- and postsynaptic adenosine receptors was examined by looking at the effects of CPA on postsynaptic membrane properties and on spontaneous or miniature excitatory postsynaptic currents (EPSCs). CPA had no detectable effect on the input resistance of phrenic moto-neurons. Moreover, the inward currents of phrenic moto-neurons in response to exogenously applied glutamate were not affected by adenosine-related compounds. On the other hand, CPA produced a significant decrease in the frequency of spontaneous and of miniature EPSCs. We conclude that adenosine can modulate transmission of inspiratory drive from bulbospinal neurons to phrenic motoneurons via presynaptic A1 receptors.